Dynamic Response of Wall Backfill Retaining System - Sreenivas Alampalli; Ahmed-W. Elgamal (Shock and Vibration)
An in situ full-scale test is conducted to measure the dynamic response of a long cantilever wall that retains backfill soil. The recorded modal parameters of this retaining wall exhibited significant similarity to those of a clamped cantilever plate (rather than those of a cantilever beam or plane-strain analysis). Such a three-dimensional (3-D) response pattern is not accounted for by current analysis procedures. A simple 3-D finite element model is employed to further analyze the observed resonant configurations. The results indicate that such configurations play an important role in the seismic response of wall backfill soil systems of variable height, such as wing walls supporting highway approach ramps.